Characterization of anti-SARS-CoV-2 monoclonal antibodies focusing on antigen binding, neutralization, and FcγR activation via formation of immune complex - Minoru Tada; Michihiko Aoyama; Akiko Ishii-Watabe (mAbs)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV−2) causes coronavirus disease 2019 (COVID−19). Antibodies induced by SARS-CoV−2 infection or vaccination play pivotal roles in the body’s defense against the virus; many monoclonal antibodies (mAbs) against SARS-CoV−2 have been cloned, and some neutralizing mAbs have been used as therapeutic drugs. In this study, we prepared an antibody panel consisting of 31 clones of anti-SARS-CoV−2 mAbs and analyzed and compared their biological activities. The mAbs used in this study were classified into different binding classes based on their binding epitopes and showed binding to the SARS-CoV−2 spike protein in different binding kinetics. A multiplex assay using the spike proteins of Alpha, Beta, Gamma, Delta, and Omicron variants clearly showed the different effects of variant mutations on the binding and neutralization activities of different binding classes of mAbs. In addition, we evaluated Fcγ receptor (FcγR) activation by immune complexes consisting of anti-SARS-CoV−2 mAb and SARS-CoV−2 pseudo-typed virus, and revealed differences in the FcγR activation properties among the binding classes of anti-SARS-CoV−2 mAbs. It has been reported that FcγR-mediated immune-cell activation by immune complexes is involved in the promotion of immunopathology of COVID−19; therefore, differences in the FcγR-activation properties of anti-SARS-CoV−2 mAbs are among the most important characteristics when considering the clinical impacts of anti-SARS-CoV−2 mAbs.